Improving the digestibility of cereal fractions of wheat, maize, and rice by a carbohydrase complex rich in xylanases and arabinofuranosidases: an in vitro digestion study. (24th September 2020) - Vangsøe, Cecilie T; Bonnin, Estelle; Joseph‐Aime, Maud; Saulnier, Luc; Neugnot‐Roux, Virginie; Bach Knudsen, Knud E
Abstract: BACKGROUND: Cereal co‐products rich in dietary fibres are increasingly used in animal feed. The high fibre content decreases the digestibility and reduces the nutrient and energy availability, resulting in lower nutritive value. Therefore, this study investigated the ability of two carbohydrase complexes to solubilize cell‐wall polysaccharides, in particular arabinoxylan (AX), from different cereal fractions of wheat, maize, and rice using an in vitro digestion model of the pig gastric and small intestinal digestive system. The first complex (NSPase 1) was rich in cell‐wall‐degrading enzymes, whereas the second complex (NSPase 2) was additionally enriched with xylanases and arabinofuranosidases. The extent of solubilization of insoluble cell‐wall polysaccharides after in vitro digestion was evaluated with gas–liquid chromatography and an enzymatic fingerprint of the AX oligosaccharides was obtained with high‐performance anion‐exchange chromatography with pulsed amperometric detection. RESULTS: The addition of carbohydrase increased the digestibility of dry matter and solubilized AX in particular, with the greatest effect in wheat fractions and less effect in maize and rice fractions. The solubilization of AX (expressed as xylose release) ranged from 6% to 41%, and there was an increased effect when enriching with xylanases and arabinofuranosidases in wheat aleurone and bran of 19% and 14% respectively. The enzymatic fingerprint of AX oligosaccharides revealed several non‐final hydrolysis products of the enzymes applied, indicating that the hydrolysis of AX was not completed during in vitro digestion. CONCLUSION: These results indicate that the addition of a carbohydrase complex can introduce structural alterations under in vitro digestion conditions, and that enrichment with additional xylanases and arabinofuranosidases can boost this effect in wheat, maize, and rice. © 2020 Society of Chemical Industry